Philosophical Prose and Logical Positivism: Examining the Relationship between Philosophical Prose and Logical Positivism (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It has been seen that we normally try to interpret the philosophical words of great philosophers. There is huge possibility that philosophies have been interpreted subjectively by generation after generation. The connotative and denotative meaning of every word is different. Thus, the philosophical meanings derived from the actual words are possibly different. In last century, much effort has been taken to consider philosophy as a science. The scientific analysis and result derived by the curious modern philosophers supported the claim of philosophy itself a science, but there was a rift in between the thinkers over to give the pure status of science to philosophy. Especially when logical positivism was introduced the discussion went to the peak. The present research paper throws a light on philosophical prose under the scanner of logical positivism.